Berlian: Belajar dengan Kreativitas Anak dalam Media Pembelajaran untuk Meningkatkan Pembelajaran Matematika - Witri Lestari; Hawa Liberna; Lin Mas Eva (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program was conducted in collaboration with the Kampung Sahabat Foundation, a social community focused on empowering and educating marginalized children, particularly children from scavenger families living around the At-Tin Mosque, Ceger, Cipayung, East Jakarta. The theme of the program was "Diamonds: Learning with Children's Creativity in Learning Media to Improve Mathematics Learning." The BERLIAN program was implemented using an educational-participatory approach that integrates the application of simple science and technology based on creativity. The implementation of the BERLIAN program at the Kampung Sahabat Foundation has had a significant positive impact in supporting the mathematics learning of scavenger children in the Cipayung area of ​​East Jakarta. This program successfully addressed the challenges of low learning motivation and difficulty understanding basic mathematical concepts through creative learning media and a fun approach. Activity achievements are classified into three categories: Immediate Results (Output), Medium-Term Results (Outcome), and Long-Term Impact (Impact).